1974
DOI: 10.1083/jcb.61.3.575
|View full text |Cite
|
Sign up to set email alerts
|

The Splitting of Hepatocyte Gap Junctions and Zonulae Occludentes With Hypertonic Disaccharides

Abstract: Mouse livers were perfused in situ through the portal vein with the disaccharides sucrose, lactose, maltose, and cellobiose in hypertonic concentrations (0 .5 M) . This treatment resulted in plasmolysis of the hepatocytes and splitting of the gap junctions and zonulae occludentes . The junctions split symmetrically, leaving a half-junction on each of the two separated cells . The process of junction splitting is followed using the freeze-fracture technique, since the junctional membranes are indistinguishable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
1

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(51 citation statements)
references
References 42 publications
2
47
1
1
Order By: Relevance
“…The fact that center-to-center values for aggregated particles in untreated Novikoff cultures average slightly less than 9-11 nm may be due to technical reasons or to an actual alteration of the 9-to 11-nm particle in conjunction with or subsequent to aggregation. In other systems, particles have been observed near the edges of junctions which appear larger than the actual junctional particles (23,28). However, more quantitative--data will be needed to confirm the role of the aggregates in coupling.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that center-to-center values for aggregated particles in untreated Novikoff cultures average slightly less than 9-11 nm may be due to technical reasons or to an actual alteration of the 9-to 11-nm particle in conjunction with or subsequent to aggregation. In other systems, particles have been observed near the edges of junctions which appear larger than the actual junctional particles (23,28). However, more quantitative--data will be needed to confirm the role of the aggregates in coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertonic extracellular solutions split hepatocyte and cardiac junctions (cf. Dewey and Barr, 1964;Goodenough and Gilula, 1974), and gap junctions separate in the presence of high concentrations of calcium chelators (Campbell and Albertini, 1981;Hirokawa and Heuser, 1982). While there is no reason to hypothesize large osmotic differences across the gap junction vesicles, abundant evidence indicates that cytoplasmic calcium activity is normally about 0.1 HM, less than that found necessary extracellularly to maintain contact between junctional membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the fate of the gap junction depends on the medium used for the dissociation procedure, and perhaps also on the tissue examined. When the tissue is treated with hypertonic sucrose or solutions with calcium buffered to submicromolar levels with chelators, gap junctions of heart (Dewey and Barr, 1965) and liver (Goodenough and Gilula, 1974;Hirokawa and Heurser, 1982) apparently split along the region of cell contact, leaving "hemichannels' in membranes of each of the previously connected cells. Alternatively, when tissue is dissociated with peptidases and solutions with calcium concentrations in the range 1-20 MM, gap junctions of heart (Muir, 1967;Severs and Powell, 1980), exocrine pancreas (Amsterdam and Jamieson, 1974), and perhaps most other tissues remain attached to one of the previously connected cells, generally with remnants of the nonfunctional membrane of the other cell attached.…”
Section: From the Departments Of Neuroscience And Physiology Albert mentioning
confidence: 99%
“…Additional studies have shown that docked connexons cannot be separated under physiological conditions (Goodenough and Gilula, 1974;Ghoshroy et al, 1995), suggesting that GJ degradation could occur via the internalization of complete double-membrane spanning GJ plaques. Structural and ultrastructural analyses of differentiating tissues and cells in culture have shown cytoplasmically located, double-membrane GJ vesicles that were termed annular gap junctions (AGJs; Ginzberg and Gilula, 1979;Larsen et al, 1979;Leach and Oliphant, 1984;Mazet et al, 1985;Jordan et al, 2001), leading to the hypothesis that AGJ vesicles represent internalized GJs.…”
Section: Introductionmentioning
confidence: 99%